2021
DOI: 10.3390/plants10081692
|View full text |Cite
|
Sign up to set email alerts
|

Response Surface Optimization of Extraction Conditions and In Vitro Antioxidant and Antidiabetic Evaluation of an Under-Valued Medicinal Weed, Mimosa pudica

Abstract: Mimosa pudica Linn is a well-known perennial herb and is traditionally used in ayurvedic medicine for the treatment of various illnesses. Despite its abundance in nature, the therapeutic potential of this invasive weed is deemed to be underappreciated in Malaysia. Previous studies have found an abundance of bioactive compounds associated with potent antioxidant properties in all parts of the plant. However, the optimum parameters required for the extraction of antioxidant compounds are still unknown. Therefore… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 53 publications
0
4
0
Order By: Relevance
“…Altemimi et al [30] concluded that the amounts of rutin and quercetin from peach and pumpkin extracts quickly increased and reached the maximum value with increasing extraction temperature from 30 to 41.08 °C and then decreased due to thermal degradation of these avonoids. Indeed, it was found that higher temperatures promoted degradation reactions such as the epimerization and oxidation of compounds, which could explain the loss of phenolic content and decrease the antioxidant and antidiabetic activities of extracts [31]. e e ect of extraction temperature was re ected in the GC-MS pro le of P. capitata ethyl acetate extracts at di erent extraction temperatures.…”
Section: Discussionmentioning
confidence: 99%
“…Altemimi et al [30] concluded that the amounts of rutin and quercetin from peach and pumpkin extracts quickly increased and reached the maximum value with increasing extraction temperature from 30 to 41.08 °C and then decreased due to thermal degradation of these avonoids. Indeed, it was found that higher temperatures promoted degradation reactions such as the epimerization and oxidation of compounds, which could explain the loss of phenolic content and decrease the antioxidant and antidiabetic activities of extracts [31]. e e ect of extraction temperature was re ected in the GC-MS pro le of P. capitata ethyl acetate extracts at di erent extraction temperatures.…”
Section: Discussionmentioning
confidence: 99%
“…While it has been observed that tannin constituents can solely be extracted using solvents possessing a dielectric constant greater than 20, such as ethanol. A plethora of research studies also have consistently demonstrated a correlation between ABTS •+ activity and the levels of total phenolic and flavonoid content (TPC and TFC) found in various plants, including P. dactylifera fruits [34] and Mimosa pudica [35]. Furthermore, previous studies have contributed to the present findings, indicating that an optimal ethanol concentration of approximately 80-85 v/v% is necessary to achieve the highest total phenolic content in Curcuma zedoaria leaves and distillery stillage from cereals [36,37].…”
Section: Response Surface Analysismentioning
confidence: 92%
“…Mimosa pudica is a medicinal plant known for its sensitive trait in which its leaves fold inward and droop as a form of defensive response. In previous reports, M. pudica has been demonstrated to possess promising antioxidant and antidiabetic properties (Baharuddin et al, 2021). The significant amount of phenols and flavonoids in M. pudica extract, especially when extracted using optimal solvent extraction techniques, has positioned it as the next valuable medicinal plant species to be regenerated in vitro.…”
Section: Introductionmentioning
confidence: 99%